THE INFLUENCE OF CROHN’S DISEASE ON THE PERIODONTAL STATUS - Irina-Georgeta Sufaru; Liliana Pasarin; Ionut Luchian; Diana-Cristala Nitescu-Kappenberg; Diana Anton; Georgeta-Maria Laza; Vladina Andronache; Sorina-Mihaela Solomon (Romanian Journal of Medical and Dental Education, 2020)
Periodontal disease and Crohn’s disease both represent inflammatory conditions. Therefore, a relationship between the pathophysiological mechanisms of these two diseases has been proposed. The manifestations of Crohn’s disease on periodontal level could surpass the oral ulcerations. The presence of gingival inflammation in patients with active digestive disease appears to be greater than when the disease is inactive. Moreover, even the clinical periodontal attachment loss could be more severe in these patients, with deep manifestations on cytokine level.